KAJIAN PENGELOLAAN SUMBER DAYA AIR UNTUK APLIKASI KONSEP ECOPARK PADA TAMAN KOTA YANG BERUKURAN BESAR DI DKI JAKARTA - Rahardjo, Petrus Nugro (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Environmental problems which happen in Jakarta metropolitan city, havealready come into a very critical condition. All surface water, such asrivers, swamps and small lakes, have extremely been continuingpolluted. Even ground water, not only the quality is getting worse, butalso the quantity is decreasing. Otherwise many swamps and smalllakes have been changing into a domestic settlement or commercialestate. One of few alternatives to cope with the problems is to manageall gardens in Jakarta by applying a new concept “Ecopark” which makesan optimizing the ecological function of a park. The concept is basedon the aim to make a friendly garden which is a part of green openspace. Through this application, especially for big gardens with thearea 5.000m2 - 10.000m2, the water resource potential will increase andits conservation will be continuously guaranteed. Garden CornelSimanjuntak dan Utama Raya are the two examples of big city gardenswhich have not been managed yet by the concept Ecopark. This activityexplained how the two gardens have to be properly managed by theconcept. The water use pattern for watering the plants, garden as thecatchment area and domestical wastewater recycling for watering arethe major ways to optimize the ecological function of gardens.